Exile, Transnational Experiences, Return, and Diasporas: Itineraries in the Southern Cone - Roniger, Luis (2024)
This article analyzes the experience of mass exile during the last wave of dictatorships in Argentina, Chile, Paraguay, and Uruguay and, in particular, the process of partial return to the countries of origin. In the face of the dramatic institutional breakdown that affected each of these societies under dictatorships in different ways and to varying degrees, the text addresses the limits, difficulties, and shortcomings that ex-exiles encountered upon their return, the impact of the returnees on their respective national scenarios, and how the transnational experience of those who suffered such territorial displacement shaped their impact on the institutions of origin, politics, and national culture upon their return to their home countries. Finally, the article shows how the countries of origin have approached and interacted with the ongoing diasporas of nationals abroad, particularly with the diaspora of academics and professionals.